Hekim Bereket’in Hulasatu't-Tıbb (25b-56a) Eseri -İnceleme, Metin, Dizin - Doğru, Gizem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Besides the literal works in Anatolia, books on medicine, history, astronomy, philosophy and Islam were also commenced to be written in Turkish as of the 14th Century. Both the copyrighted and also translated books on medicine draw attentions at present and serve as a source for researchers in various fields. This study handles the copy of “Hulâsatu’t- Tıbb”, one of the first copyrighted books on medicine written in Turkish by Hekim Bereket in the 14th Century, which is registered in the library of Paris Bibliotheque Nationale under pressmark 171. An Examination-Text-Index study was carried on the 30-leaf section of the book between leafs 25b-56a to provide source for the Old Anatolian Turkish period, Turkish language and History of Medicine. Key words: Hekim Bereket, Old Anatolian Turkish, History of Medicine, Turkish Language.

ÖZ XIV. yüzyıldan itibaren Anadolu’da edebî eserlerin yanı sıra Türkçe olarak tıp, tarih, astronomi, felsefe ve İslâm dini ile ilgili eserler yazılmaya başlanmıştır. Gerek telif gerekse çeviri olarak yazılan tıp eserleri, günümüzde ilgi çekmekte ve farklı alanlarda çalışan birçok araştırmacıya kaynak niteliği taşımaktadırlar. Bu çalışmada, Hekim Bereket tarafından XIV. yüzyılda yazılmış, Anadolu’da telif edilen ilk Türkçe tıp eserlerinden biri olan Hulāsatu’t-Tıbb’ın Paris Bibliotheque Nationale kütüphanesinde 171 numarada kayıtlı olan nüshası ele alınmıştır. Eserin 25b-56a varakları arasındaki 30 varaklık bölüm üzerinde İnceleme-Metin-Dizin çalışması yapılmış, Eski Anadolu Türkçesi dönemi, Türk dili ve tıp tarihi alanlarına kaynak sağlanması amaçlanmıştır. Anahtar Kelimeler: Hekim Bereket, Eski Anadolu Türkçesi, Tıp Tarihi, Türk Dili.
Türk Dili ve Edebiyatı Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Fen ve Edebiyat Fakültesi, Türk Dili ve Edebiyatı Bölümü, 2015. Tez Danışmanı: Yard. Doç. Dr. Emel Gözlü.
Keywords: Türk Dili ve Edebiyatı; Hekim Bereket -14. yy Hulasatu't Tıbb; Hekim Bereket; Eski Anadolu Türkçesi; Tıp Tarihi; Türk Dili; Old Anatolian Turkish; History of Medicine; Turkish Language